2008
DOI: 10.1111/j.1365-2966.2008.13713.x
|View full text |Cite
|
Sign up to set email alerts
|

Photometric characterization of a well-defined sample of isolated galaxies in the context of the AMIGA project

Abstract: We perform a detailed photometric analysis (bulge–disc–bar decomposition and Concentration‐Asymmetry‐Clumpiness – CAS parametrization) for a well‐defined sample of isolated galaxies, extracted from the Catalog of Isolated Galaxies and reevaluated morphologically in the context of the Analysis of the interstellar Medium of Isolated GAlaxies project. We focus on Sb–Sc morphological types, as they are the most representative population among the isolated spiral galaxies. Our analysis yields a large number of impo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
80
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(96 citation statements)
references
References 106 publications
(166 reference statements)
15
80
1
Order By: Relevance
“…The rate of AGN candidates, derived from IRAS colors and radio continuum emission of the AMIGA galaxies is lowest compared to similar studies from the literature . Optical photometric analysis of Sb-Sc galaxies in the AMIGA sample showed that most galaxies have pseudo-bulges instead of classical bulges, and a comparison with samples of spiral galaxies selected without isolation criteria revealed that the isolated galaxies tend to host larger bars, are more symmetric, less concentrated and less clumpy (Durbala et al 2008). These findings strongly support that the AMIGA sample represents the most isolated galaxies in the local Universe where secular evolution is dominant.…”
Section: Introductionsupporting
confidence: 69%
“…The rate of AGN candidates, derived from IRAS colors and radio continuum emission of the AMIGA galaxies is lowest compared to similar studies from the literature . Optical photometric analysis of Sb-Sc galaxies in the AMIGA sample showed that most galaxies have pseudo-bulges instead of classical bulges, and a comparison with samples of spiral galaxies selected without isolation criteria revealed that the isolated galaxies tend to host larger bars, are more symmetric, less concentrated and less clumpy (Durbala et al 2008). These findings strongly support that the AMIGA sample represents the most isolated galaxies in the local Universe where secular evolution is dominant.…”
Section: Introductionsupporting
confidence: 69%
“…Our studies suggest that the most isolated galaxies show different properties than less isolated field samples. AMIGA early-type galaxies are usually fainter than late-types in the B-band and most spirals in our sample appear to host pseudo-bulges and not classical bulges (Verdes-Montenegro et al 2005;Sulentic et al 2006;Durbala et al 2008b). AMIGA spiral galaxies are redder than similar type galaxies in close pairs, showing a Gaussian distribution of the (g − r) colours with a smaller median absolute deviation (almost half) compared to galaxies in wide and close pairs.…”
Section: Introductionmentioning
confidence: 94%
“…The original CIG contains 1051 items, but one of the compiled objects is a globular cluster (CIG 781;Verdes-Montenegro et al 2005) so the size of the sample considered in the rest of this paper is N = 1050. The AMIGA project also started several multiwavelength studies for galaxies in the CIG: characterisation of the B-band luminosity function (Sulentic et al 2006); Fourier photometric decomposition, optical asymmetry, and photometric clumpiness and concentration (Durbala et al 2008(Durbala et al , 2009); characterisation of the FIR luminosity function (Lisenfeld et al 2007), radiocontinuum ), molecular gas (Lisenfeld et al A9, page 2 of 14 2012), and atomic gas (Espada et al 2011); characterisation of nuclear activity (Sabater et al , 2012; optical colours (Fernández Lorenzo et al 2012); and optical study of the stellar mass-size relation (Fernández Lorenzo et al 2013). …”
Section: Amiga Projectmentioning
confidence: 99%
“…It is a first step in trying to identify and better understand isolated galaxies in the local Universe. Durbala et al (2008) used a subsample of 100 typical CIG galaxies (Sb, Sbc, and Sc) and found that most of them have a bulge-to-total luminosity ratio B/T < 0.1. If B/T is a measure of environmental dynamical processing (MacArthur et al 2010), galaxies in the CIG sample appear to be very little affected by it.…”
Section: Introductionmentioning
confidence: 99%